"Ahorita estamos en lo nuestro" (Now We Are Ouselves"): Afor- Venezuelan Music Rituals for Health and Community Wellbeing - Katrin Lengwinat (Legon Journal of the Humanities, 2016)
In Venezuela, people of West African descent developed rituals for wellbeing within Catholic contexts. This study analyses performances directed at fulfilling health-related desires. The first is ritual street performance staged as part of Corpus Christi,under the name of the Devils of Corpus Christi. It includes instrumental music, dance, special clothing, theatrica lity and high symbolism. The second performance is the Feast of Saint John, celebrated with drums, songs, dances and rituals. These ritual music festivities also present communal benefits like solidarity, pleasure and unity, since people can express their unique identities through them and use them as acts of resistance.